(untitled) (Journal of the College of Basic Education, 2022)
The causes and consequences of political violence have become major topics of research in an era of history weighed down by seemingly continual warfare, revolution, and other violent acts of every description. The study of the politics of violence, on the other hand, has drawn upon theoretical perspectives and forms of analysis from all the social and political sciences. The problematicof violence and its justification is a concern not only for scientists and politicians but also for artists and playwrights. Many playwrights have endeavored to display the argument of violence and its politics in their works. Among those playwrights are John Arden and Harold Pinte